GENETIC ANALYSIS OF SNPS IN CANDIDATE GENES ASSOCIATED WITH DROUGHT TOLERANCE IN GOSSYPIUM HERBACEUM. - ASHISH KUMAR GUPTA (International Journal of Pharma and Bio Sciences, 2015)
Drought tolerance is an important physiological phenomenon for any agricultural crop in the depletion of ground water scenario. Recent case-control transcriptome and association studies have identified a network of genes underlying with the complex trait. We aimed to determine whether some of the genes confer drought tolerance in the Levant cotton (Gossypium herbaceum L.) population and thus to establish an association of SNPs in candidate genes with drought tolerance severity in Levant cotton with respect to Upland and Egyptian cotton population. This study analyzed leaf DNA isolated from 20 genotypes of G. herbaceum and 10 genotypes of allotetraploid species. A comparative in silico analysis of microarray and transcriptome data of G. herbaceum and G. hirsutum concluded few putative genes like blue-copper binding protein (BCB), UDP-Glucosyltransferase (ATUGT85A3), DNA binding/transcription factor (CAPRICE), senescence-associated genes (ATLEA5,SAG21), lipid transfer protein 4 (LTP4), DNAJ heat shock protein, trehalose-phosphatase (TPS6, ATTPS6), zinc finger (CCCH-type) family protein, dark inducible 6 (DIN6), Ethylene forming enzyme (EFE), acid phosphatase/protein serine/threonine phosphatase (PAP10), those played a significant role during drought tolerance. Out of these genes, six with SNPs (accession number yet to be submitted)–snp55, snp298, snp306, snp365, snp365, snp560 and snp574– were genotyped using Snapshot kit (ABI, USA) in high-throughput 96-capillary DNA analyzer 3730xl (ABI, USA) with G. herbaceum, G. hirsutum, G. barbadense collected from different major cotton research stations in India. Our results suggest that a sequence variant on snp574 and snp55 are two important loci that confer high cross-species drought tolerance.